Theory and Methodology of Teaching Foreign Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article provides an in-depth exploration of teaching methodology, particularly in the context of Foreign Language Teaching (FLT). It emphasizes the interdisciplinary nature of methodology, integrating insights from various sciences. The use of the passive voice throughout maintains a formal tone and scholarly objectivity. The discussion encompasses the components of the educational process, the role of linguistics and psychology, and the evolution of teaching methods within FLT. The concluding remarks underscore the historical context and contributions of antecedent methods, contributing to a comprehensive overview of the subject.